(untitled) (Vietnam Journal of Community Medicine, 2024)
Aspiration pneumonia is a lung infection caused by inhaling saliva, food, liquids, vomit, and even small foreign objects. It can be treated with appropriate medication. If left untreated, complications can be serious, even fatal. We record and report a case of aspiration pneumonia due to a swallowing disorder following complications of shingles ear. The patient received intensive medical treatment according to an appropriate regimen combined with a feeding method through a gastrostomy. The treatment process was quite difficult, but the patient recovered spectacularly.